Pengembangan Strategi Pembelajaran Aplikasi Simulasi Tanggap Darurat Bencana Banjir pada Mahasiswa Keperawatan - Tawil, Selviana; Wijayaningsih, Kartika Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to develop a simulation application-based learning strategy to improve the readiness of nursing students in dealing with flood disaster emergency response situations. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach. The study showed a significant increase in students' emergency response skills after using the application. The average pretest score was 65.3 and increased to 84.7 in the posttest, with a statistically significant difference (p-value <0.05). This scenario-based simulation application has proven effective in improving various aspects of student readiness, including the ability to identify risk situations, communicate effectively in teams, make decisions, and first aid and evacuation skills. In addition, this application received a positive response from students, who felt more confident in dealing with emergencies after practicing using the application. In conclusion, this application has the potential to be integrated into the nursing education curriculum as an additional effective learning media in emergency response training. Keywords: Flood Disaster, Scenario-Based Learning, Emergency Response Simulation, Learning Strategy